Features of the contract for engineering services in civil law of Ukraine: ways to improve the process in the context of improving business - Glado, Yuliya; Yavorska, Oleksandra; Tarasenko, Leonid; Tsilmak, Olena; Matiienko, Tetiana (Business: Theory and Practice, 2021)
The current state of regulation of the engineering services market in the world is at the level of constant development and improvement. The formation of a system for concluding contractual relations in the field of engineering services is no exception. The imperfection of the system for concluding the contract for engineering services indicates the weak state of the current management system in the field of innovation and intellectual property in the field of doing business both in a single country and throughout the world, which necessitates revising and improving the principles of concluding contracts in the field of engineering services. The contract for engineering services appeared in the world legislation relatively recently, in science there is still no unity in understanding the nature of this contract, as well as in the terminology used to designate legal relations arising on its basis. There are different, sometimes polar, approaches to the essence, features and elements of the contract for engineering services. In addition, there is still no single mechanism for forming a contract. Given this, an important step towards improving the contract for engineering servicess in civil law will be the formation of a systematic sequence of steps using the IDEF0 functional model. In this regard, the main goal of the article is to form the basic principles of consistency and algorithmization of the process of concluding the contract for engineering servicess on the basis of a functional model IDEF0.